Diffusion tensor and susceptibility-weighted imaging in concussion assessment of national football league players. Issue 5 (11th March 2013) - Luther, Neal; Niogi, Sumit; Kutner, Kenneth; Rodeo, Scott; Shetty, Teena; Warren, Russell; Weiss, Leigh; Barnes, Ronnie; Zimmerman, Robert; Tsiouris, Apostolos; Hartl, Roger
Abstract : Introduction: Standard MRI is normal following the vast majority of concussions. Diffusion tensor imaging (DTI) and susceptibility-weighted imaging (SWI) are advanced MRI techniques hypothesized to be more sensitive in detecting subtle evidence of structural brain injury. Using DTI and SWI in National Football League (NFL) players, we aim to elucidate and localise the presence of such injury following concussions. Methods: This ongoing prospective study has recruited active NFL players with and without history of concussion within 6 months prior to entry. Neurological and neurocognitive examination, DTI, and SWI were performed on each subject. Blinded neuroradiologists performed radiographic analysis. Fractional anisotropy (FA) values were measured for 11 distinct white matter tracts on DTI. A global FA value was calculated. SWI was utilised to assess for microhemorrhage. Statistical comparisons between players with and without recent concussion, and to civilian controls, were made. Results: Seven of eighteen evaluated players to date had a concussion within 6 months of entry. On DTI, of the 11 tracts evaluated, a significant decrease in FA for concussed players was seen in one tract. There was no significant difference in global FA assessment between players with and without recent concussions. Civilian control comparisons are ongoing. SWI was negative in all players. Conclusions: To our knowledge this is the largest prospective brain imaging study, and the first utilising DTI and SWI to assess anatomical injury secondary to concussion, in NFL players. Minimal changes have been observed in players with recent concussion. The clinical significance of these findings remains under investigation. Learning Objectives: By the conclusion of the session, participants should be able to (1) understand the role of DTI and SWI in the evaluation of mild traumatic brain injury (2) discuss to what degree long-term football play poses risk in terms of structural brain injury. References: Concussion, football, MRI, NFL. How will your Research Improve Patient Care: There is no reliable objective test to evaluate the severity of brain injury suffered secondary to concussion, and concussion is a growing area of concern in football and other contact sports. This study evaluates to what degree brain injury as detected by highly sensitive MR technologies (DTI and SWI) is suffered by those who have had long-term, high-level participation in football and now play at the professional level. Information from this study could play an important role in establishing neurological risks of football.